Amelogenesis imperfecta in familial hypomagnesaemia and hypercalciuria with nephrocalcinosis caused by CLDN19 gene mutations. Issue 1 (16th August 2016) - Yamaguti, Paulo Marcio; Neves, Francisco de Assis Rocha; Hotton, Dominique; Bardet, Claire; de La Dure-Molla, Muriel; Castro, Luiz Claudio; Scher, Maria do Carmo; Barbosa, Maristela Estevão; Ditsch, Christophe; Fricain, Jean-Christophe; de La Faille, Renaud; Figueres, Marie-Lucile; et al.
Abstract : Background: Amelogenesis imperfecta (AI) is a group of genetic diseases characterised by tooth enamel defects. AI was recently described in patients with familial hypercalciuria and hypomagnesaemia with nephrocalcinosis (FHHNC) caused by CLDN16 mutations. In the kidney, claudin-16 interacts with claudin-19 to control the paracellular passage of calcium and magnesium. FHHNC can be linked to mutations in both genes. Claudin-16 was shown to be expressed during amelogenesis; however, no data are available on claudin-19. Moreover, the enamel phenotype of patients with CLDN19 mutations has never been described. In this study, we describe the clinical and genetic features of nine patients with FHHNC carrying CLDN19 mutations and the claudin-19 expression profile in rat ameloblasts. Methods: Six FHHNC Brazilian patients were subjected to mutational analysis. Three additional French patients were recruited for orodental characterisation. The expression profile of claudin-19 was evaluated by RT-qPCR and immunofluorescence using enamel epithelium from rat incisors. Results: All patients presented AI at different degrees of severity. Two new likely pathogenic variations in CLDN19 were found: p.Arg200Gln and p.Leu90Arg. RT-qPCR revealed low Cldn19 expression in ameloblasts. Confocal analysis indicated that claudin-19 was immunolocalised at the distal poles of secretory and maturing ameloblasts. Conclusions: For the first time, it was demonstrated that AI is associated with FHHNC in patients carrying CLDN19 mutations. The data suggest claudin-19 as an additional determinant in enamel formation. Indeed, the coexistence of hypoplastic and hypomineralised AI in the patients was consistent with claudin-19 expression in both secretory and maturation stages. Additional indirect systemic effects cannot be excluded.